The impact of adverse childhood experiences on therapy outcome in adolescents engaging in nonsuicidal self-injury - Edinger, Alexandra; Fischer-Waldschmidt, Gloria; Parzer, Peter; Brunner, Romuald; Resch, Franz; Kaess, Michael (Frontiers in psychiatry, 2020)
Objective: Nonsuicidal self-injury (NSSI) is a prevalent and clinically significant behavior. There is a substantial association between adverse childhood experiences (ACEs) and NSSI. However, there are no studies, investigating the impact of ACEs on NSSI treatment (psychotherapy) outcome. The aim of this secondary analysis of a randomized controlled trial (RCT) on psychotherapy of NSSI was to investigate the relationship between ACEs and treatment outcome in adolescents engaging in NSSI. Method: A sample of 74 adolescent outpatients engaging in repetitive NSSI (incidents on ≥ 5 days within the last six months) was recruited for a RCT. ACEs were assessed by the Childhood Experience of Care and Abuse (CECA) interview before treatment onset. Based on the CECA, participants were divided in two groups: with a history of ACEs (n = 30) and without a history of ACEs (n = 44). Frequencies of NSSI, depression, suicide attempts as well as quality of life were measured at three points in time: before treatment onset (baseline; T0), 4 (T1) and 10 months (T2) after treatment onset. Results: Both participants with and without ACEs were able to reduce the frequency of NSSI significantly [χ²(1) = 26.72; p < .001]. Surprisingly, participants with ACEs reached a significantly greater reduction in NSSI frequency within the past six months compared to participants without ACEs [χ²(1) = 5.08; p = .024]. There were also substantial and similar improvements regarding depressive symptoms, suicide attempts and quality of life in both groups. Conclusion: ACEs seem to positively predict treatment response in psychotherapy for adolescent NSSI. This is contrary to prior research suggesting ACE as an unfavorable prognostic factor in the treatment of mental disorders. Clinical trial registration information - Kurzzeittherapie bei selbstschädigenden und riskanten Verhaltensweisen im Jugendalter; http://www.drks.de; DRKS00003605.